Direct observation of electronic inhomogeneities induced by point defect disorder in manganite films - Sirena, Martin (2010)
We have investigated the influence of point defect disorder in the electronic properties of manganite films. Real-time mapping of ion irradiated samples conductivity was performed though conductive atomic force microscopy (CAFM). CAFM images show electronic inhomogeneities in the samples with different physical properties due to spatial fluctuations in the point defect distribution. As disorder increases, the distance between conducting regions increases and the metal-insulator transition shifts to lower temperatures.  Transport properties in these systems can be interpreted in terms of a percolative model. The samples saturation magnetization decreases as the irradiation dose increases whereas the Curie temperature remains unchanged.